(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
This article presents the results obtained through a documentary and bibliographical review of documents from scientific articles during the period 2015-2022 on the importance of the role of pedagogical innovation with the purpose of strengthening technological development that promotes the growth of education. Colombian agroindustrial sector. Based on the analysis of the publications consulted, the categories related to the pedagogical tools that have been developed in the field of knowledge teaching in the agro-industrial sector were addressed, as well as the main innovations that have been adopted in the main production chains of the Colombian agro-industrial sector. such as sugar cane, coffee, cocoa and cereals, and the impact that these innovations have had on the growth of the sector for the period 2015-2022. When analyzing the growth potential of the agro-industrial sector in Colombia, it is concluded that the strengthening of technological capacities is key, but for this, professionals with skills in the management of new technologies must be trained, for which innovative pedagogical tools are required that enable this purpose to be achieved.